Secular trend of the body height in the Polish industrial region - Puch, Elżbieta Alicja (Anthropological Review, 1994)
The aim of the study was to attempt to assess changes over the last twenty years in the body height of children and adolescents, aged from seven to eighteen years, from the Upper Silesian industrial region of Poland. The data concerning the body height of 1413 children from Katowice, which were collected in 1986, were compared with the mean values of the stature of children and adolescents from Silesian cities where the data were collected between 1964 and 1974. Growth change per decade in each sex-age category was calculated and age-specific curves for secular trends were constructed. These were compared with curves for other industrialised and nonindustrialised regions in the world. In the Upper Silesia the mean values of the body height of children and adolescents of both sexes were measured over the last twenty years. The mean values for puberty rose more than the same values for preand post-puberty. This trend is more clearly marked in boys. Age specific secular trend curves for children from Upper Silesia have an irregular pattern and are significantly different in both sexes. The comparison of our data with data for children and adolescents from other parts of the world (Fig. 3-6) shows that our data adhere to the regular pattern of secular changes that are characteristic for industrial regions. The nature of the age-specific secular trend pattern suggests periodic fluctuations in living conditions. These fluctuations have a negative effect on the physical development of the children concerned.